Right to be forgotten. Freedom of expression and information - Olivero Cepeda, Morfis Estarkin (2022)
With the rise of new technologies, the growth of mass data processing and the digitization of newspaper archives, the individual information of people that is available in digital media has begun to cause great concern. It is not uncommon to see people constantly concerned about their personal information that appears on the internet, and it is that our image online worries us more every day. In this way, people who considered their reputation and honor affected by personal information hosted on the Internet and linked to their name and surname, due to issues that happened in the past or for which they were investigated, submitted their corresponding claims to European authorities. The authorities decided, through important resolutions and sentences that are exposed in the present work, and that mainly deal with the prevalence of the right to data protection of the interested party, the right to freedom of expression or the right to freedom of information that users have. It is sought through these lines to ensure that readers get to know the jurisprudential line that the European courts have on the prevalence of these rights.